Implementasi Program Budidaya Tanaman Hortikultura Sebagai Upaya Ketahanan Pangan di Desa Pagerwojo Kecamatan Buduran Kabupaten Sidoarjo - Fauziah, Lusi Indri; Mursyidah, Lailul (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This study discusses the implementation of the food security program in Pagerwojo Village, Buduran District, Sidoarjo Regency through horticultural plant cultivation. This program aims to increase food independence and improve the welfare of the Pagerwojo Village community. However, the implementation of the food security program in Pagerwojo Village faces various obstacles such as the absence of bookkeeping for harvest results which makes it difficult to measure productivity, the absence of technology in storing harvest results, and the lack of adequate training for community group members in managing horticultural crops. The methodology is a qualitative, descriptive technique. The six variables in this study—policy standards and targets, resources, implementing agent characteristics, inter-organizational communication, implementers' attitudes, and economic, social, and political environments—were examined using Van Metre and Van Horn's theory of public policy implementation.Based on the results of the study, it shows that although the implementation of the food security program experienced several obstacles, community involvement, economic support, and appropriate political policies have made Pagerwojo Village an example of how food security programs can be implemented effectively in a rural context.